2012
DOI: 10.1002/aic.13949
|View full text |Cite
|
Sign up to set email alerts
|

Drag force and clustering in bubble swarms

Abstract: In this article, results of detailed numerical simulations are reported meant to provide a closure relation for the drag force acting on bubbles rising in a dense swarm. The formation of clusters of bubbles in a periodic domain and the effect thereof on the rise velocity and effective drag coefficient on the bubbles are studied. Using smaller bubble sizes than presented in our earlier work, we are also able to refine our correlation for the drag coefficient acting on bubbles rising in a swarm, such that it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 25 publications
(44 reference statements)
2
35
0
Order By: Relevance
“…amount of exchanging interface (gas-solid interface in their case). However, bubbles have a tendency to cluster horizontally (Roghair et al, 2013b), meaning that situations arise where many bubbles are found in a plane perpendicular to the vertical direction. Moreover, another difference is that our simulations do not use a predefined flow or pressure gradient over the domain, but the liquid flow is purely driven by the rising bubbles.…”
Section: Zero Concentration Inflow Boundariesmentioning
confidence: 99%
“…amount of exchanging interface (gas-solid interface in their case). However, bubbles have a tendency to cluster horizontally (Roghair et al, 2013b), meaning that situations arise where many bubbles are found in a plane perpendicular to the vertical direction. Moreover, another difference is that our simulations do not use a predefined flow or pressure gradient over the domain, but the liquid flow is purely driven by the rising bubbles.…”
Section: Zero Concentration Inflow Boundariesmentioning
confidence: 99%
“…A remarkable set of papers 5,6,[13][14][15] study bubbly flows in which the interaction between the flow and a large number of bubbles is studied. In particular, turbulent flows can be significantly affected by bubbliness.…”
mentioning
confidence: 99%
“…When the bubbles start to form a horizontal cluster we see a large drop in the Reynolds number, which results in a considerable drop of the Sherwood number (about 16%). As explained by [25], the clustering we see here is likely to be a result of the domain size, since n b =n b;max (where n b ¼ 8, and n b;max is the maximum number of bubbles that can align in a horizontal plane, calculated for this case using Eq. (6) of [25] to be 9.5) is about 0.84, which is close to 1.…”
Section: Resultsmentioning
confidence: 96%
“…As explained by [25], the clustering we see here is likely to be a result of the domain size, since n b =n b;max (where n b ¼ 8, and n b;max is the maximum number of bubbles that can align in a horizontal plane, calculated for this case using Eq. (6) of [25] to be 9.5) is about 0.84, which is close to 1. That means that we expect to see bubbles clustered in one horizontal plane.…”
Section: Resultsmentioning
confidence: 96%